FENOMENA SINGKATAN DAN SLANG DALAM KOMUNIKASI CHAT DIGITAL: KAJIAN LINGUISTIK TERHADAP EFISIENSI KOMUNIKASI DAN PERUBAHAN BAHASA - Athaya Maharani Nurusyaika; Najwa Asna; Alvika Lutfitamulia; Imam Baehaeqie (Jurnal PENEROKA, 2026)
This study aims to analyze the form, function, and impact of the use of abbreviations and slang on communication efficiency and language change from a linguistic perspective. The development of digital communication technology has influenced language usage patterns, particularly in chat-based communication on social media and instant messaging applications. The scope of the study focuses on the use of abbreviations and slang in digital conversations on the WhatsApp, Instagram, and Telegram platforms used by users aged 18–24 years. This study emphasizes the dynamics of digital language use in everyday communication. The study uses a descriptive qualitative approach based on linguistic and sociolinguistic theories. Data analysis was conducted using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The research data consists of 50 chat conversations from 15 digital media users collected through observation and documentation techniques during January–February 2026. The results show that the use of abbreviations and slang can increase communication efficiency by simplifying language forms so that messages can be conveyed more quickly and practically. In addition, the use of slang functions as a marker of social identity and linguistic creativity of digital media users. Research findings also indicate that abbreviations represent processes of clipping, abbreviation, acronyms, and phonological reduction, while slang reflects semantic shift. However, excessive use of non-standard language has the potential to influence the use of standard Indonesian in formal contexts, necessitating the ability to adapt language variations to the communication context.